Pengaruh Konsentrasi Gliserol Terhadap Karakteristik Fisik Dan Kimia Edible Film Dari Pati Ubi Jalar Ungu (Ipomoea batatas l. poir) - Yuliana Ndruru; Ambar Rukmini; masrukan; Dyah Titin Laswati (Universitas Widya Mataram, 2025)
Damage to fresh food such as fruits and vegetables due to exposure to air and humidity has become a common problem in the community. One innovative solution to maintain food quality is the use of starch-based edible films. This study aims to determine the effect of glycerol concentration on the physical and chemical characteristics of a starch-based edible film of purple sweet potato (Ipomoea batatas L.). The study was conducted using a Complete Random Design (RAL) with five treatments of glycerol concentrations of 6%, 8%, 10%, 12%, and 13% (v/b starch). The parameters tested include tensile strength, elongation, thickness, folding, moisture transmission rate (WVTR), and moisture content. The results showed that the increase in glycerol concentration had an effect on all the physical characteristics of edible films, except WVTR. Edible films with a glycerol concentration of 13% show the best characteristics with the highest elongation values (4.39%), highest folding (28 folds), thickness (0.07 mm), tensile strength (12.60 MPa), WVTR (0.02g/cm2.h) and moisture content (17.68%). Meanwhile, the best edible film chemical characteristics according to the 1995 SNI standard are at a glycerol concentration of 8% (15.77). Overall, all concentrations of purple sweet potato starch have met some of the standard parameters of commercial edible films. However, it still lags behind in terms of elongation, moisture content and tensile strength. However, this edible film has enough potential for use in small-scale or household packaging applications.